MELD score and clinical type predict prognosis in hepatorenal syndrome: Relevance to liver transplantation - ÖZDOĞAN, OSMAN CAVİT (My University, 2005)
Important progress has been made recently regarding the pathogenesis and treatment of hepatorenal syndrome (HRS). However, scant information exists about factors predicting outcome in patients with cirrhosis and HRS. Moreover, the prognostic value of the model of end-stage liver disease (MELD) score has not been validated in the setting of HRS. The current study was designed to assess the prognostic factors and outcome of patients with cirrhosis and HRS. The study included 105 consecutive patients with HRS. Forty-one patients had type I HRS, while 64 patients had type 2 HRS. Patients with type I HRS not only had more severe liver and renal failure than type 2 patients, they also had greater impairment of circulatory function, as indicated by lower arterial pressure and higher activation of vasoconstrictor factors. In the whole series, the median survival was 3.3 months. In a multivariate analysis of survival, only HRS type and MELD score were associated with an independent prognostic value. All patients with type 1 HRS had a high MELD score (>= 20) and showed an extremely poor outcome (median survival: 1 mo). By contrast, the survival of patients with type 2 HRS was longer and dependent on MELD score ( >= 20, median survival 3 mo; < 20, median survival 11 mo; P <.002). In conclusion, the outcome of patients with cirrhosis and HRS can be estimated by using two easily available variables, HRS type and MELD score. These data can be useful in the management of patients with HRS, particularly for patients who are candidates for liver transplantation.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Hepatoloji; Gastroenteroloji; Hepatology; Gastroenterology